2009
DOI: 10.1177/0146167209339628
|View full text |Cite
|
Sign up to set email alerts
|

The Racing-Game Effect: Why Do Video Racing Games Increase Risk-Taking Inclinations?

Abstract: The present studies investigated why video racing games increase players' risk-taking inclinations. Four studies reveal that playing video racing games increases risk taking in a subsequent simulated road traffic situation, as well as risk-promoting cognitions and emotions, blood pressure, sensation seeking, and attitudes toward reckless driving. Study 1 ruled out the role of experimental demand in creating such effects. Studies 2 and 3 showed that the effect of playing video racing games on risk taking was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 31 publications
12
102
2
7
Order By: Relevance
“…A similar set of experiments demonstrated that increases in the accessibility of risk-promoting thoughts and in actual risky driving behaviors following exposure to racing games is mediated by the individual's perception of themself as a reckless driver (Fischer et al, 2009). Risky driving behavior was greater in men than women and when the participant was the player rather than the observer of a racing game.…”
Section: Need For Speed: Racing Video Games and Risk-takingmentioning
confidence: 96%
See 4 more Smart Citations
“…A similar set of experiments demonstrated that increases in the accessibility of risk-promoting thoughts and in actual risky driving behaviors following exposure to racing games is mediated by the individual's perception of themself as a reckless driver (Fischer et al, 2009). Risky driving behavior was greater in men than women and when the participant was the player rather than the observer of a racing game.…”
Section: Need For Speed: Racing Video Games and Risk-takingmentioning
confidence: 96%
“…Study 1 expands on previous work with racing video games (Beullens et al, 2011;Fischer et al, 2009;Beullens et al, 2008;Fischer et al, 2007) by examining multiple genres of video games and attitudes towards risk in domains that are unrelated to the video game environment Sensitivity to feedback (i.e., increased sensitivity to reward, decreased sensitivity to punishment) is one pathway through which the reinforcement contingencies utilized by video games may alter risky decision making. Study 2 was also designed to expand the generalizability of previous work that demonstrated a relationship between video game experience and sensitivity to positive and negative picture stimuli (Bailey et al, 2011;Bartholow et al, 2006).…”
Section: Overview Of the Current Studiesmentioning
confidence: 98%
See 3 more Smart Citations